MOTIVASI MEMPELAJARI BAHASA JEPANG MAHASISWA PRORGAM STUDI PENDIDIKAN BAHASA JEPANG ANGKATAN 2017 FKIP UNIVERSITAS RIAU - Dhika Afriyani; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research discusses about the motivation of the students in Japanese Education program of Riau University. The aim of this research is to measure the motivation of students and what would affect the said motivation on the matter of studying Japanese language. To conduct the research, the writer examined 57 of the students in Japanese Education program of Riau University from the generation of year 2017. The method used was quantitative descriptive research method. The result of this research is that the motivation of the students in Japanese Education program of Riau University from the generation of year 2017 could be classified as strongly motivated. The motivation of 2017 generation is more or less 73.13%. This research also brings light to what kind of factors which would affect the motivation to study of the students. The factors are; the subject and the facility of the lesson, and the presence of other person. 29.82% of the students disagrees that the myriads of subjects about conjugation makes them eager to study. 26.31% of the students agreed that the lack of facility to study makes them eager to study. 54.38% of the students agreed that studying with friends could help them in understanding the subject of Japanese Language.Key Words : Motivation, Studying Japanese Language